Lysate of Parabacteroides distasonis prevents severe forms of experimental autoimmune encephalomyelitis by modulating the priming of T cell response - Jiraskova Zakostelska, Zuzana; Kraus, Michal; Coufal, Stepan; Prochazkova, Petra; Slavickova, Zaneta; Thon, Tomas; Hrncir, Tomas; Kreisinger, Jakub; Kostovcikova, Klara; Kleinova, Pavlina; Lizrova Preiningerova, Jana; Pavelcova, Miluse; et al. (Frontiers in Immunology, 2024)
The gut microbiota influences the reactivity of the immune system, and Parabacteroides distasonis has emerged as an anti-inflammatory commensal. Here, we investigated whether its lysate could prevent severe forms of neuroinflammation in experimental autoimmune encephalomyelitis (EAE) in mice and how this preventive strategy affects the gut microbiota and immune response. Lysate of anaerobically cultured P. distasonis (Pd lysate) was orally administered to C57BL/6 mice in four weekly doses. One week later, EAE was induced and disease severity was assessed three weeks after induction. Fecal microbiota changes in both vehicle- and Pd lysate-treated animals was analyzed by 16S V3–V4 amplicon sequencing and qPCR, antimicrobial peptide expression in the intestinal mucosa was measured by qPCR, and immune cell composition in the mesenteric and inguinal lymph nodes was measured by multicolor flow cytometry. Pd lysate significantly delayed the development of EAE and reduced its severity when administered prior to disease induction. EAE induction was the main factor in altering the gut microbiota, decreasing the abundance of lactobacilli and segmented filamentous bacteria. Pd lysate significantly increased the intestinal abundance of the genera Anaerostipes, Parabacteroides and Prevotella, and altered the expression of antimicrobial peptides in the intestinal mucosa. It significantly increased the frequency of regulatory T cells, induced an anti-inflammatory milieu in mesenteric lymph nodes, and reduced the activation of T cells at the priming site. Pd lysate prevents severe forms of EAE by triggering a T regulatory response and modulating T cell priming to autoantigens. Pd lysate could thus be a future modulator of neuroinflammation that increases the resistance to multiple sclerosis.